2020
DOI: 10.2478/rtuect-2020-0061
|View full text |Cite
|
Sign up to set email alerts
|

Effect of N:P Ratio on Microalgae/Nitrifying Bacteria Community in Agro-Digestate Treatment

Abstract: The role of P content on the treatment and valorization of the liquid fraction of digestate, namely centrate, through microalgae-based technologies was evaluated in this study. The performance of four column photobioreactors, which were fed on diluted centrate with corrected (10 mg N/ mg P) and not modified (129 mg N/ mg P) N:P ratio, were monitored and compared. The results demonstrated that P shortage in the centrate affected neither the total nitrogen and COD removal rate nor the volumetric biomass producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Different medium characteristics and environmental and operational conditions can greatly affect microalgae or nitrifying bacteria, and shift their equilibrium [31,52]. The most important factors related to both microalgae and nitrifying bacteria activity are depicted in Figure 2 and discussed below.…”
Section: Factors Influencing Microalgae-nitrifying Bacteria Cultivationmentioning
confidence: 99%
See 2 more Smart Citations
“…Different medium characteristics and environmental and operational conditions can greatly affect microalgae or nitrifying bacteria, and shift their equilibrium [31,52]. The most important factors related to both microalgae and nitrifying bacteria activity are depicted in Figure 2 and discussed below.…”
Section: Factors Influencing Microalgae-nitrifying Bacteria Cultivationmentioning
confidence: 99%
“…This behaviour was reported by González-Camejo et al [32], who observed an equilibrium between microalgae and bacteria when the ammonium loading rate was under 30-35 mg N•L -1 •d -1 , but a significant proliferation of nitrifying bacteria when it went over 40 mg N•L -1 •d -1 . Other authors have also reported nitrification control by adjusting the N:P ratio of the influent [31]. If phosphorus is scarce in the medium, nitrifying bacteria will not be able to grow.…”
Section: Control Of Nutrient Loadsmentioning
confidence: 99%
See 1 more Smart Citation
“…High ammonium oxidation is quite common in microalgae-based technologies treating municipal and agro-zootechnical digestate [34,54,55], especially if phosphorus is readily available [65]. The elevated P concentration in the centrate favored the activity of the AOB [66], which are the main responsible for ammonium oxidation. This hypothesis is supported also by the positive correlation between the ammonium oxidation rate and the concentration of PO 4…”
Section: Environmental Parameters Biomass Productivity and Nutrientsmentioning
confidence: 99%